Пошаговое объяснение:
(х-5)²+(3-x)²-4(x+5)(3-x)-48=(x+1)²
х^2-10х+25+х^2-6х+9-4(3х+15-х^2-5х)-48=
=х^2+2х+1
х^2-10х+25+х^2-6х+9+8х-60+4х^2-48=
х^2-10х+25+х^2-6х+9+8х-60+4х^2-48-
-х^2-2х-1=0
5х^2-10х-75=0 |:5
х^2-2х-15=0
D=√(-2)^2-4*(-15)=√64
D=8
x1=(2-8)/2=-3
x2=(2+8)/2=5
Пошаговое объяснение:
(х-5)²+(3-x)²-4(x+5)(3-x)-48=(x+1)²
х^2-10х+25+х^2-6х+9-4(3х+15-х^2-5х)-48=
=х^2+2х+1
х^2-10х+25+х^2-6х+9+8х-60+4х^2-48=
=х^2+2х+1
х^2-10х+25+х^2-6х+9+8х-60+4х^2-48-
-х^2-2х-1=0
5х^2-10х-75=0 |:5
х^2-2х-15=0
D=√(-2)^2-4*(-15)=√64
D=8
x1=(2-8)/2=-3
x2=(2+8)/2=5